LIMNOLOGICAL ASPECTS OF A SHALLOW POND USED AS RECEIVER AQUACULTURE WASTES AND FOR AGRICULTURAL IRRIGATION - Lúcia Helena SIPAÚBA-TAVARES; Juliane dos Santos Alves da SILVA; Rodrigo Ney MILLAN; Gislaine Costa de MENDONÇA (Boletim do Instituto de Pesca)
Water samples, zooplankton community and sediment samples were analyzed at three sites in a pond receiving wastes, bi-weekly for seven months, covering the rainy and dry seasons. Water quality parameters failed to show significant differences between the sites for turbidity, total suspended solids, dissolved oxygen, transparency, conductivity, alkalinity and total phosphorous. Only temperature was different between the seasons. In the case of sediment, only aluminum (Al) was not different during the experimental period when highest calcium (Ca) concentrations were reported. The relative abundance of Rotifera during the sampling period reached 80-96% (rainy season) and 59-98% (dry season) in total zooplankton. Current study demonstrated that the water quality of shallow pond associated with allochthonous materials from aquaculture farm significantly influenced the structure of zooplankton assemblage due to high nutrient concentrations, conductivity, alkalinity and chlorophyll-a causing more fertilized water. However, heavy rains (February-April) and continuous water flow favored aeration (dissolved oxygen >5.2 Â± 1 mg L-1). The use of pond water for agricultural irrigation or for other purposes, must be analyzed more effectively, avoiding problems caused by its usage.